POSITION OF CENTRAL EUROPEAN REGIONAL AIRPORTS - Tatiana REMENCOVÁ (Silesian University of Technology, 2021)
This article focuses on the position of regional airports in the countries of Central Europe, with a focus on the airports of the Visegrád Group, especially the airports in Slovakia and the Czech Republic. The authors explain the financing of the airports and provision of state aid to these entities according to European legislation. This article reports differences in the national implementation processes of the same Europeans rules in the V4 Member State and compares the regime of financing of the regional airports. Subsequently, we analyse the economic situation of regional airports and their state based on financial indicators. In general, the current COVID-19 pandemic has exacerbated their situation. Many countries still adhere to strict regulations or international travel bans so as not to spread the virus. The sharp decline in the number of passengers and flights has begun to have an impact on the financial viability of regional airports; therefore, financial assistance for regional airports will be more than necessary in the coming years.